Mode of commuting to school and its association with physical activity and sedentary habits in young Ecuadorian students (2018)
Active commuting to and from school (ACS) could help to increase daily physical activity levels in youth; however, this association remains unknown in Ecuadorian youth. Thus, the aims of this study were (1) to determine the patterns of commuting to and from school and (2) to analyze the associations between ACS, physical activity (PA), and sedentary habits in Ecuadorian youth. A total of 732 students (65.3% males), aged 10–18 years (children = 246, young adolescents = 310, older adolescents = 162) from the central region of Ecuador participated in this study. A self-report questionnaire, including the usual mode and frequency of commuting, distance from home to school (PACO-Questionnaire), and PA and sedentary habits (YAP-Questionnaire), was used. Most of the sample lived ?2 km from school; however, they were mainly passive commuters (96%). The most common mode of commuting was by car (to school = 43.4%, from school = 31.6%; p less than 0.001). Children presented significantly higher scores (0–4) in PA outside school and total PA compared with older adolescents (2.20 ± 0.97 vs. 1.97 ± 0.96; p = 0.013 and 2.30 ± 0.76 vs. 2.09 ± 0.74, p = 0.019, respectively), as well as the lowest scores in sedentary habits (1.51 ± 0.65, p less than 0.001). PA at school and total PA were positively associated with ACS (OR 3.137; 95% CI, 1.918 to 5.131; p less than 0.001, and OR 2.543; 95% CI, 1.428 to 4.527; p = 0.002, respectively). In conclusion, passive modes of transportation were the most frequently used to commute to and from school in young Ecuadorians. PA at school and total PA were positively associated with ACS. Thus, interventions at school setting could be an opportunity to improve PA levels and additionally ACS in youth from the central region of Ecuador. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.